The London 2012 Olympics: A gender equality audit - Donelly, P.; Donelly, M. K. (2013)
The Centre for Sport Policy Studies (CSPS), which is part of the Faculty of Kinesiology and Physical Education at the University of Toronto, has published a research report on gender equality in sport looking at the example of the 2012 London Olympics. The authors of the study recognise a tendency among major women's sports organisations to increasingly emphasise women's representation in sports leadership rather than merely looking into female participation in sport events. Nonetheless the study reveals ongoing gender inequalities with regard to the athletes in as much as gender-based structural and regulatory differences still exist in the Olympic programme. In fact in 2012 there were 30 more medal events for men than for women, and in total 1.233 more men than women participated in the Olympics. Accordingly the report recommends to ensure a similar amount of events and medal opportunities for both sexes, while appealing to the IOC to take responsibility for respective measures.